Haraceas in the Trnje profile - Knez, Martin (Acta carsologica, 1996)
Within the Kozina beds of the Trnje profile there appear horizons of "Type B: oogonia horizons" among the various types of Haracea horizons; Haraceas evidence characteristics of transport. It is presumed that oogonia were carried along by water currents towards relatively deeper parts of the sedimentary basin. Within the limestone beds, at the transport from the parts with no oogonia into the sediments containing numerous oogonia of Haracea, there are no sedimentological changes.
Keywords: geologija; geology; karbonatne kamnine; sedimentacija; sedimentne kamnine; stratigrafija; stratigraphy; Trnje